2006
DOI: 10.5194/nhess-6-741-2006
|View full text |Cite
|
Sign up to set email alerts
|

On Es-spread effects in the ionosphere connected to earthquakes

Abstract: Abstract. In the present work, phenomena in the ionosphere are studied, which are connected with earthquakes (16 events) having a depth of less than 50 km and a magnitude M larger than 4. Analysed are night-time Es-spread effects using data of the vertical sounding station PetropavlovskKamchatsky (ϕ=53.0 • , λ=158.7 • ) from May 2004 until August 2004 registered every 15 min. It is found that the maximum distance of the earthquake from the sounding station, where pre-seismic phenomena are yet observable, depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
1
14
0
2
Order By: Relevance
“…The influence of seismic events on the lower ionospheric layers, i.e., the upper wall of the waveguide along which VLF signals are propagated, was confirmed by results of measurement of ionospheric parameters. In particular, the results reported by other authors (Liperovskaya et al, 2003;Liperovsky et al, 2005) showed that 3 days before the earthquake the turbulence level in the sporadic E s layer of the ionosphere ARTICLE IN PRESS Fig. 6.…”
Section: Discussionmentioning
confidence: 82%
“…The influence of seismic events on the lower ionospheric layers, i.e., the upper wall of the waveguide along which VLF signals are propagated, was confirmed by results of measurement of ionospheric parameters. In particular, the results reported by other authors (Liperovskaya et al, 2003;Liperovsky et al, 2005) showed that 3 days before the earthquake the turbulence level in the sporadic E s layer of the ionosphere ARTICLE IN PRESS Fig. 6.…”
Section: Discussionmentioning
confidence: 82%
“…How ever, such pre cur sors are not eas ily re corded and are sub ject to in tru sion by ra dio waves. In more re cent years, there has been a fo cus on the de tec tion of ion o spheric anom a lies in pre cur sor re search (Liu et al 2001Pulinets 2004;Hegai et al 2006;Heki et al 2006;Liperovskaya et al 2006;Hayakawa 2007). This body of re search has con firmed some ion o spheric anom a lies having re la tion ships with earth quakes, but such re la tion ships have not been suit ably math e mat i cally de scribed; they have re lied on ob ser va tional anal y ses, which can be sub jec tive.…”
mentioning
confidence: 99%
“…This area of study is aimed at using such anomalies to establish earthquake prediction models (Hayakawa 2007;Heki et al 2006;Liperovskaya et al 2006;Liu et al 1996Liu et al , 2001Liu et al , 2006Hegai et al 2006). showed that by using the daily cross-correlation coefficient for ionospheric TEC between two ionosondes (one covering the epicenter of the earthquake and the other hundreds of kilometers Date away) it was possible to identify statistically TEC anomalies occurring up to 7 days before mainshock nucleation.…”
Section: Introductionmentioning
confidence: 99%